Color Image Steganography Using Discrete Wavelet Transformation and Optimized Message Distribution Method - Mazumder, Juned Ahmed; Hemachandran, Kattamanchi (International Journal of Computer Sciences and Engineering, 2014)
Steganography is the science of concealing secret information into any digital media such as images, audio, video etc so that no eavesdropper can empathies this secret communication. In this paper we have propounded a high security steganographic technique using discrete wavelet transformation and optimized message dispersing method. Here we have used Haar wavelet transformation which decomposes the cover image into high frequency and low frequency information and high frequency information contains information about the edges, corners etc. of the image where we have dispersed our secret information. Secret Message is inserted into all the color components of high frequency sub-bands that are Red, Green and Blue color components starting from the last column of each of the color components from top to bottom depending upon the length of the message. To measure the imperceptibility of the proposed steganography method we have used MSE and PSNR. For this experiment we have taken four image formats: PNG, BMP, JPEG and TIFF and we have inserted the secret message of sizes starting from 2 KB to 20 KB and evaluated their corresponding MSR and PSNR using standard method. Besides the analysis of MSE and PSNR we have also evaluated the message insertion and the message extraction time. Our experimental result shows that the MSE and Capacity are improved with acceptable PSNR compared to other methods.